GPs' perspectives on managing the NHS Health Check in primary care: a qualitative evaluation of implementation in one area of England. Issue 7 (7th July 2016) - Shaw, Rachel L; Lowe, Helen; Holland, Carol; Pattison, Helen; Cooke, Richard
Abstract : Objectives: To evaluate the implementation of the National Health Service (NHS) Health Check programme in one area of England from the perspective of general practitioners (GPs). Design: A qualitative exploratory study was conducted with GPs and other healthcare professionals involved in delivering the NHS Health Check and with patients. This paper reports the experience of GPs and focuses on the management of the Heath Check programme in primary care. Setting: Primary care surgeries in the Heart of Birmingham region (now under the auspices of the Birmingham Cross City Clinical Commissioning Group) were invited to take part in the larger scale evaluation. This study focuses on a subset of those surgeries whose GPs were willing to participate. Participants: 9 GPs from different practices volunteered. GPs served an ethnically diverse region with areas of socioeconomic deprivation. Ethnicities of participant GPs included South Asian, South Asian British, white, black British and Chinese. Methods: Individual semistructured interviews were conducted with GPs face to face or via telephone. Thematic analysis was used to analyse verbatim transcripts. Results: Themes were generated which represent GPs' experiences of managing the NHS Health Check: primary care as a commercial enterprise ; ' buy in' to concordance in preventive healthcare ; following protocol and support provision . These themes represent the key issues raised by GPs. They reveal variability in the implementation of NHS Health Checks. GPs also need support in allocating resources to the Health Check including training on how to conduct checks in a concordant (or collaborative) way. Conclusions: The variability observed in this small-scale evaluation corroborates existing findings suggesting a need for more standardisation. Further large-scale research is needed to determine how that could be achieved. Work needs to be done to further develop a concordant approach to lifestyle advice which involves tailored individual goal setting rather than a paternalistic advice-giving model.